Pengaruh Karakteristik Perusahaan terhadap Kualitas Audit dan Struktur Modal - Hadiani Fitriani; Nuraeni (CV. Satria Jaya, 2023)
This study aims to examine the effect of company characteristics on audit quality and capital structure. Company characteristics in this study are measured by firm size, profitability, and asset structure. Audit quality is measured by audit fee, audit delay, and audit size. As well as capital structure as measured by debt to total equity (DER), long term debt to total equity (LTDER), and debt to total assets (DAR). This study uses partial least square (PLS) analysis. The sample of this research is agro-industrial companies listed on the Indonesia Stock Exchange for the period 2013-2018. The results of this study found that company characteristics had a negative effect on audit quality. This study also found that company characteristics have a negative effect on capital structure. And this study also found that audit quality has a positive effect on capital structure, this indicates that the better the audit quality, the better the capital structure of the company.